Design Study of Full Scale Accelerator Driven System (ADS), for Transmuting High Level Waste of MA/Pu - Marsodi Marsodi; K. Nishihara; Z. Suud (PPIKSN-BATAN, 2008)
The ADS system used in this study consisting of a high intensity proton linear accelerator, a spallation target, and a sub-critical reactor core. The Pb-Bi spallation target is bombarded by high intensity protons coming from the accelerator. The fast neutrons generated from the spallation reaction were used to drive the sub-critical reactor core. In this ADS system, the neutron source is in the center of reactor core region, so that the neutron distribution was concentrated in the center of core region. In this case, the B/T of MA/Pu could be performed effectively in the center of core region. The neutron energy in the outer region of reactor core was decreased due to the moderation of fuel and coolant materials. Such condition gives a chance to perform Burning and/or Transmutation of LLFPs.The basic parameters of this system are shown in the form of neutronic design, neutron spectrum and B/T rate, including other aspects related to the safety operation system. Furthermore, the analysis of the ADS system was accomplished using ATRAS computer code of the Japan Atomic Energy Research Institute, JAERI[1]. Due to the complexity of the reactor calculation codes, the author has carried out only those calculations needed for analyzing the neutronics system and some parameters related to the safety system. Design study of the transmutation system was a full-scale power level system of 657.53 MWt sub-critical reactor for an accelerator-driven transmutation system. The liquid Pb-Bi was used together as the spallation target materials and coolant of the system, because of some advantages of Pb-Bi in the system concerning the comparison with the sodium coolant. Moreover, they have a possibility to achieve a hard neutron energy spectrum, avoid a positive void reactivity coefficient, allow much lower system operating temperatures, and are favorable for safety in the event of coolant leakage. The multiplication factor of sub-critical core design was adjusted exclusively through the high intensity protons beam accelerator at the spallation target. The fuel was assumed to have homogeneous compositions in the form of (MA-Pu) ZrN mixture with 15N enriched. The compositions of Pu and MA were the same with the compositions of UO2 fuel from 33-GWd/t burn-up in PWRs spent fuel after 5 year cooling. The results have been compared with the spent fuel composition from 45 and 60 GWd/t burn-up in PWRs at the same cooling time. The calculation of the burn-up step was 730 days per one batch reloading by using 4-regions core calculation model. The specific parameters of ADS system used in the calculation are described in Table1.